Wind power generator with wireless detection device - YANG CHUYUN (2013)
The utility model relates to a wind power generator with a wireless detection device. The wind power generator comprises a power generator, a supporting rod, a base, a wind guide cover, a wind guide duct, an impeller, a control circuit and a storage battery. The supporting rod is arranged on the base and connected with the power generator, the impeller is arranged on an rotary shaft of the power generator, the wind guide duct is arranged outside the impeller and connected with the wind guide cover, the control circuit is connected with the storage battery and the power generator which are in connection, a control device which is the wireless detection device is arranged on the control circuit, a wind inlet of the wind guide duct is consistent with the wind guide direction of the wind guide cover, and an inlet where the wind guide duct guides wind into the power generator is consistent with the direction that the impeller is started to rotate. The wind power generator with the wireless detection device is simp